2015
DOI: 10.1038/nmeth.3283
|View full text |Cite
|
Sign up to set email alerts
|

Mapping native disulfide bonds at a proteome scale

Abstract: We developed a high-throughput mass spectrometry method, pLink-SS (http://pfind.ict.ac.cn/software/pLink/2014/pLink-SS.html), for precise identification of disulfide-linked peptides. Using pLink-SS, we mapped all native disulfide bonds of a monoclonal antibody and ten standard proteins. We performed disulfide proteome analyses and identified 199 disulfide bonds in Escherichia coli and 568 in proteins secreted by human endothelial cells. We discovered many regulatory disulfide bonds involving catalytic or metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 34 publications
5
127
0
3
Order By: Relevance
“…The software was also adapted to enable mapping of disulfide bonds within numerous proteins, termed 'pLink-SS' [120]. Using pLink-SS along with MS analysis, 199 disulfide bonds in 150 proteins of E. coli have been identified by comparing disulfide proteomes in dsbA À , dsbC À (DsbA and DsbC are thiol-disulfide oxidoreductases) and wild-type BW25113 strains [121].…”
Section: Oxmrmmentioning
confidence: 99%
See 1 more Smart Citation
“…The software was also adapted to enable mapping of disulfide bonds within numerous proteins, termed 'pLink-SS' [120]. Using pLink-SS along with MS analysis, 199 disulfide bonds in 150 proteins of E. coli have been identified by comparing disulfide proteomes in dsbA À , dsbC À (DsbA and DsbC are thiol-disulfide oxidoreductases) and wild-type BW25113 strains [121].…”
Section: Oxmrmmentioning
confidence: 99%
“…In addition, 309 disulfide bonds and 1738 glutathionylated sites were identified in A549 cells under diamide treatment. Moreover, when monitoring the distance of two cysteine residues forming disulfide bonds, they found that CXXC is the most prominent mode in disulfide bonds-formation in E. coli, and the formation of disulfide bonds could occasionally alter protein conformations by expelling metal ions [120]. Disulfide proteome analysis provides new concepts for exploring redox-sensitive proteins and mapping disulfide bonds critical for protein function.…”
Section: Oxmrmmentioning
confidence: 99%
“…(2014)pLink-SSHCD or high-resolution ETDHCD MS2A: Automatic workflow with FDR estimation, disulfide-specific ions and internal ions are considered, works for complex samples;L: highly complex forms such as three peptides inter-linked through two disulfide bonds cannot be identifiedLu et al . (2015)…”
Section: Introductionmentioning
confidence: 99%
“…This method was published in 2015 (Lu et al . 2015). Since then, to our knowledge, it has been used successfully in dozens of studies and seven of them have been published (Hartman et al .…”
Section: Introductionmentioning
confidence: 99%
“…It follows that modification or mutation of these key cysteines must be avoided. Finally, an increasing number of proteins are now recognized as possessing conserved disulfide bonds (Lu et al, 2015). Although thiol-specific probes will generally not react with cysteines that are involved in a disulfide linkage, the addition of extra cysteines into recombinant proteins can potentially lead to aberrant, nonphysiological disulfide formation.…”
Section: Introductionmentioning
confidence: 99%